Fabrication and testing of small capacity solar desalination system using humidification - dehumidification method - ANIL BABU A. K; Pravitha M; Er. Priya G. Nair (Guide) (Tavanur 2012 Department of Land and Water Resources and Conservation Engineering)
Fabrication and testing of small capacity solar desalination system using humidification - dehumidification method
Fabrication and testing of small capacity solar desalination system using humidification - dehumidification method